2005
DOI: 10.1159/000081133
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Effects of Physical Therapy in Different Intensities of Urodynamic Stress Incontinence

Abstract: Purpose: The aim of this study was to investigate and compare the short-term effects of a physical therapy program in patients with different intensities of urodynamic stress urinary incontinence (USI). Subjects and Methods: 48 patients with USI were assigned to three groups according to the intensity of their incontinence: group I: 0–2 g (n = 17), group II (mild intensity: >2–10 g, n = 16) and group III (moderate intensity: >10 g, n = 15) as determined by the 1-hour pad test. A physical therapy program compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 54 publications
0
27
1
Order By: Relevance
“…IF electrical stimulation has been implicated in the management of urinary incontinence and for pain control [11]. In a recent study, Koklu et al [21] reported IF to be effective in decreasing constipation symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IF electrical stimulation has been implicated in the management of urinary incontinence and for pain control [11]. In a recent study, Koklu et al [21] reported IF to be effective in decreasing constipation symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in females with stress incontinence to treat urinary incontinence resulting from an overactive bladder [10]. This modality is also used for pain reduction and wound healing in adults [11].…”
Section: Introductionmentioning
confidence: 99%
“…10 Investigations 11-13 demonstrated similar effectiveness of different SEPFM programs, but no evidence of a specific, standardized program. These investigations differ regarding the parameters used in the training programs: eight [14][15][16] 10,19,22 In general, SEPFM is effective in the treatment of female SUI; however, there is a great heterogeneity of programs, not allowing identification of the most effective protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Though "skill training" has been quoted as useful for PFM training, few information on the specificity of these exercises have been made available. Other studies (Arvonen et al, 2000;Balmforth et al, 2004;Dumoulin et al, 2004;Hay-Smith et al, 2002;Parkkinen et al, 2004;) Turkan, 2005), even match up PFM strengthening exercises with "skill training", getting positive results, but as the reports don't follow a standard protocol, comparisons become invalid. The role of the abdominal muscles has also been discussed, as far as PFM training and strengthening are concerned (Cammu & Nylen, 1998;Johnson, 2001;Pieber et al, 1995).…”
Section: Pelvic Floor Muscle Trainingmentioning
confidence: 99%